Alzheimer’s disease and oral health: what we know so far - Jurczenko, Lidia; Semianiuk, Alina; Miejska-Kamińska, Marta (Nursing Problems / Problemy Pielęgniarstwa, 2026)
Alzheimer’s disease (AD) has been increasingly associated with poor oral health, including periodontal disease, tooth loss, and oral dysbiosis. This review summarizes current evidence linking oral health and AD, with an emphasis on oral pathogens, systemic inflammation, and cognitive decline. A literature review conducted up to June 30, 2025, identified 20 eligible studies. Individuals with AD consistently showed oral dysbiosis, characterized by increased levels of Porphyromonas gingivalis, Fusobacterium nucleatum, and Tannerella forsythia, and decreased levels of commensals such as Streptococcus and Rothia. Periodontitis and tooth loss were independently associated with greater AD risk. A large cohort study of over 32.6 million individuals reported more than a twofold increased AD risk among those with poor oral health. These findings support the potential role of oral hygiene as a modifiable and cost-effective preventive strategy against AD.